The Implementation of AI and Immersive Technology in E-Commerce: The Role of Customer Engagement as a Mediating Variable - Aliyah, Kisti Nur; Rizqiana, Zulfanita Dien (UIN Raden Mas Said Surakarta, 2024)
The headway of information and communication technology has led to significant changes in various industries, particularly in e-commerce. The integration of artificial intelligence (AI) and immersive technologies such as augmented reality (AR) and virtual reality (VR) has created new opportunities for e-commerce to improve customer experiences. This study analyzes the effects of implementing AI and immersive technology in e-commerce, focusing on customer engagement as a mediating factor. A sample of 99 participants was examined and analyzed using PLS-SEM by SmartPLS 4 software, and the findings indicate that AI and immersive technology have a positive, significant impact on online purchase intention. Customer engagement cannot mediate the relationship between artificial intelligence and online purchase intention. However, it does mediate the relationship between immersive technology and online purchase intention. Keywords: Artificial Intelligence; Immersive technology; Customer Engagement; Purchase Intention; e-commerce